Faster computation of non-zero invariants from graph based method - Abdul Hameed, Vazeerudeen (Springer-Verlag, 2012)
This paper presents a study of geometric moment invariants generated from graph based algorithms. One of the main problems addressed was that the algorithms produced too many graphs that resulted in zero moment invariants. Hence, we propose an algorithm to determine zero moment invariant generating graphs. Induction proof of the steps involved in the algorithm has also been presented with suitable example graphs. It has been found and illustrated with examples that the computational time for identifying non-zero invariants could be largely reduced with the help of our proposed algorithm.